Pelibatan Akad IjÄrah dalam Praktik Rahn di Bank Syariâ€™ah Perspektif Hukum Ekonomi Syariah - Wahid, Nur (Fakultas Syariah IAIN Purwokerto, 2018)
The involvement of lease (ijÄrah) contract in pawn practice in syariâ€™ah bank resulted in a combination of contract known as multi-â€˜aqd. Concerning multiple contracts (multi-â€˜aqd), there are a number of Prophetic traditions, at least three hadiths that are outwardly (textual meaning) indicating a ban on the use of multiple covenants. For example, the hadith about the prohibition of trading and debts (baiâ€™ wa salaf), the prohibition to trade with two contracts (baiâ€™atain fÄ« baiâ€™ah), and two sales and purchase contracts in one transaction (á¹£afqatain fÄ« á¹£afqah). The contract of lease (ijÄrah) and the pawn agreement (rahn) are two different types of contract, in which the lease includes the type of sale and purchase agreement, while the pawn includes the type of loan contract. This combination of contracts is a type of multi-contract which is prohibited based on the hadith above. Transactions with this multi-contract form almost exist in all Islamic banking products today. This paper concludes that the law of engagement of lease contracts in pawn practices in Islamic banks is allowed. The Islamic jurisprudence scholars argue that this combination of contracts is compatible with the purpose of sharia (maqÄá¹£id al-sharÄ«â€™ah), namely the ease in muamalah, lightening in the burden, and provide opportunities for innovation and the relevance of the development of the times and human needs in transactions.